Nickel-coated glass/epoxy honeycomb sandwich composite for broadband RCS reduction. (15th June 2020) - Kwak, Byeong-Su; Choi, Won-Ho; Noh, Yeong-Hoon; Jeong, Gi-Won; Yook, Jong-Gwan; Kweon, Jin-Hwe; Nam, Young-Woo
Abstract: In this paper, a new proposed radar-absorbing honeycomb sandwich composite with nickel-coated glass fabric, implemented via electroless plating, was applied to the leading edge of a NACA 0012 wing airfoil model to reduce the echo radar cross-section (RCS) level. The composite was designed and fabricated without dispersing conductive nanoparticles or metal magnetic micropowders in polymer materials. The proposed composite exhibited −10 dB microwave absorption in the frequency range of 5.8–16.3 GHz, with a resonance peak of −38.1 dB at 8.2 GHz under TM mode, and an RCS reduction of 10 dB for VV polarization and 8 dB for HH polarization in the frequency range of 6.0–17.8 GHz. When the proposed absorber was applied to the leading edge of NACA 0012, the simulated echo RCS level was reduced by 10 dB from C-band to Ku-band under both horizontal and vertical polarizations. A flatwise compressive test was conducted to evaluate mechanical performance of the composite. The proposed composite can be potentially applied to the radar-absorbing structure of stealth aircrafts. Highlights: Nickel-coated glass fabric was fabricated using electroless plating. Fabric was used in honeycomb sandwich composite and applied to wing airfoil model. Proposed composite reduced echo radar-cross section level of wing-shaped structures. Composite demonstrates potential as radar-absorbing structure for stealth aircrafts.